Analysis of Reliability, Transaction Speed, and User Experience on Information System Integration in E-commerce Business in Indonesia - Wily Mohammad; Etika Purnamasari; Hanifah Nurul Muthmainah; Loso Judijanto (West Science Information System and Technology, 2023)
This research investigates the dynamics of information system integration in the context of e-commerce businesses in Indonesia, focusing on the critical factors of reliability, transaction speed, and user experience. Employing a quantitative approach, the study utilizes Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze data from a sample of 175 participants. The measurement model assessment reveals robust factor loadings and reliability measures, establishing the foundation for further analysis. Discriminant validity analysis highlights the distinctiveness of the constructs, though attention to refining measurement items for user experience is recommended. The model fit assessment indicates that the proposed structural model aligns well with the observed data. The structural model analysis uncovers significant positive relationships between reliability, transaction speed, user experience, and information system integration. Furthermore, the R-Square values underscore the substantial impact of these factors, explaining approximately 60.2% of the variance in information system integration. The findings provide valuable insights for businesses and policymakers, emphasizing the need to prioritize reliability, transaction speed, and user experience to enhance information system integration in Indonesian e-commerce.